What determines the share of labour in national income? A cross-country analysis - Marta Guerriero; Kunal Sen (Institute for the Study of Labor (IZA), 2012)
Recent evidence on functional income distribution suggests that the shares of capital and labour in national income vary considerably both over time and across countries. Specifically, there seems to be a general reduction in the labour share around the world, in particular from the mid-1980s onwards. Using fixed effects regression methods on a panel dataset covering 89 countries - both developing and developed - over the period 1970-2009, this study examines the mechanisms underlying the variability in the labour share. In particular, it focuses on the relationships between the labour share and measures of international trade and technological change. The results are robust across different specifications, for yearly data as well as 3- and 5-year averages, and after performing instrumental variable estimation. They suggest that trade openness and technological innovation have a positive and significant effect on the labour share. However, Foreign Direct Investments inflows and mechanisation seem to be negative drivers. Moreover, other factors, such as the level of economic development, education, and the strength of the regulations in the labour market, seem to also significantly influence functional distribution of income.
Keywords: E25; F16; J30; 330; labour share of income; functional income distribution; globalisation; technological progress; Lohnquote; Funktionelle Einkommensverteilung; Globalisierung; Technischer Fortschritt; Schätzung; Welt